(In)visible Minorities and the Law in England - Gino G. Raymond (Revue Française de Civilisation Britannique)
This article evokes the contradictions of the English judicial system and the political class with regard to the rights of citizens from minority communities, notably Muslim ones. Whether it is violence aimed at women, the interpretation of marriage rights or the defence of a sectarian notion of community, English courts are sometimes inclined to tolerate citizens behaving in a way that is characterised by particularism and inequality. The report by Lord Scarman after the Brixton riots, followed by Lord Macpherson’s on the death of the teenager Stephen Lawrence, would appear to have opened the door to an interpretation of racism which hinders the willingness of the authorities to intervene in certain communities, and which might be seen to challenge the principle of equality underlying the concept of citizenship.